2000
DOI: 10.1029/2000jb900140
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature magnetic properties of pelagic sediments (Ocean Drilling Program Site 805C): Tracers of maghemitization and magnetic mineral reduction

Abstract: range measured. The divergence may be caused by the low-temperature stabilization of spontaneous magnetization vectors along with exchange interaction in the magnetitemaghemite system. Together, maghemitization and magnetic reduction diagenesis appear to play a dominant role in controlling the low-temperature properties of the sediment studied. As a result, low-temperature magnetic studies may provide more information on differences in reduction diagenesis than on the distribution of bacterial magnetite in nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 53 publications
9
116
0
Order By: Relevance
“…In contrast, CIE samples exhibit a weak Verwey transition (T v ) depressed $20 K, which suggests the presence of nonstoichiometric SD magnetite. The lowtemperature remanence behavior of CIE samples is typical of a mixture of detrital and biogenic magnetite [Moskowitz et al, 1993;Smirnov and Tarduno, 2000;Weiss et al, 2004], an interpretation supported by our TEM results (Figures 4a and 4c). Moreover, Moskowitz et al [1993] suggest that dZFC and dFC can indicate the presence of biogenic magnetic and discriminate it from detrital or other authigenic forms in bulk sediment samples [see also Weiss et al, 2004].…”
Section: Pa4104supporting
confidence: 76%
“…In contrast, CIE samples exhibit a weak Verwey transition (T v ) depressed $20 K, which suggests the presence of nonstoichiometric SD magnetite. The lowtemperature remanence behavior of CIE samples is typical of a mixture of detrital and biogenic magnetite [Moskowitz et al, 1993;Smirnov and Tarduno, 2000;Weiss et al, 2004], an interpretation supported by our TEM results (Figures 4a and 4c). Moreover, Moskowitz et al [1993] suggest that dZFC and dFC can indicate the presence of biogenic magnetic and discriminate it from detrital or other authigenic forms in bulk sediment samples [see also Weiss et al, 2004].…”
Section: Pa4104supporting
confidence: 76%
“…54 Nonetheless, FeO domains can be shown to form kinetically as interim phases at interfaces from oxidation to hematite or reduction to magnetite. 43 It has been found that FeO can exist in three crystal structures, namely B1 (NaCl structure, ), B2 (CsCl structure, ), and B8 (NiAs, P6 3 mc), 55 56 All this suggests that in fact gradations of oxygen stoichiometry are expected for iron oxide core-shell particles.…”
Section: Results and Discussion A Structural Characterizationmentioning
confidence: 99%
“…The offsets were more noticeable for the HM sample group. Large FC-ZFC offsets are typically seen for goethite [Guyodo et al, 2006, Carter-Stiglitz et al, 2006, and much smaller ones in multidomain (> 1 μm), partially oxidized, magnetite [Smirnov and Tarduno, 2000]. Both phases probably contribute to the FC/ZFC behavior, but because of the very large differences in the intrinsic saturation magnetization between magnetite/maghemite and goethite, the former dominates in these series of measurements.…”
Section: Low-temperature Magnetic Properties: Fc Zfc and Rtsirmmentioning
confidence: 99%